Prolactin promotes a partial recovery from the atrophy of both male and female gerbil prostates caused by castration - Zanatelli, Marianna (2021)
Background: The male and female prostates are controlled by steroid hormones, suffering important morphological and physiological changes after castration. Prolactin is involved in the regulation of the male prostate, having already been identified in the tissue, acting through its receptor PRLR. In the Mongolian gerbil, in addition to the male prostate, the female prostate is also well developed and active in its secretion processes. The aim of the present study was to evaluate the effects of exposure to exogenous prolactin in the prostate of both intact and castrated male and female gerbils in order to establish if prolactin administration can sustain prostate cell activity in conditions of sexual hormone deprivation. Methods: The morphological analyses were performed by biometric analysis, lesion histological analysis and morphometric-stereological aspects. In addition, immune-cytochemical tests were performed for prolactin and its receptor, as well as for the receptors of androgen and oestrogen and serum prolactin dosage. All data were submitted to ANOVA or Kruskal-Wallis tests for comparison between groups. P < 0.05 was considered to be statistically significant. Results: The results showed a strong influence of prolactin on the morphology of the prostate, with the development of important epithelial alterations, after only 3 days of administration, and an expressive epithelial cell discard process after 30 days of administration. Prolactin acts in synergy with testosterone in males and mainly with oestrogens in females, establishing different steroid hormonal receptor immunoreactivity according to sex. It was also demonstrated that prolactin can assist in the recovery from some atrophic effects caused in the gland after castration, without causing additional tissue damage. Conclusions: The prolactin and its receptor are involved in the maintenance of the homeostasis of male and female gerbils, and also cause distinct histological alterations after exogenous exposure for 3 and 30 days. The effects of prolactin are related to its joint action on androgens and oestrogens and it can also assist in the recovery from the atrophic effects of castration.